Inflammatory stimulation preserves physiological properties of retinal ganglion cells after optic nerve injury - Stutzki, Henrike; Leibig, Christian; Andreadaki, Anastasia; Fischer, Dietmar; Zeck, Günther (Frontiers in Cellular Neuroscience, 2014)
Axonal injury in the optic nerve is associated with retinal ganglion cell (RGC) degeneration and irreversible loss of vision. However, inflammatory stimulation (IS) by intravitreal injection of Pam3Cys transforms RGCs into an active regenerative state enabling these neurons to survive injury and to regenerate axons into the injured optic nerve. Although morphological changes have been well studied, the functional correlates of RGCs transformed either into a de- or regenerating state at a sub-cellular level remain unclear. In the current study, we investigated the signal propagation in single intraretinal axons as well as characteristic activity features of RGCs in a naive, a degenerative or a regenerative state in ex vivo retinae one week after either optic nerve cut alone (ONC) or additional inflammatory stimulation (ONC+IS). Recordings of single RGCs using high-density microelectrode arrays demonstrate that the mean intraretinal axonal conduction velocity significantly decreased within the first week after ONC. In contrast, when ONC was accompanied by regenerative Pam3Cys treatment the mean intraretinal velocity was undistinguishable from control RGCs, indicating a protective effect on the proximal axon. Spontaneous RGC activity decreased for the two most numerous RGC types (ON- and OFF-sustained cells) within one post-operative week, but did not significantly increase in RGCs after inflammatory stimulation. The analysis of light-induced activity revealed that RGCs in ONC animals respond on average later and with fewer spikes than control RGCs. IS significantly improved the responsiveness of the two studied RGC types. These results show that the transformation into a regenerative state by IS preserves, at least transiently, the physiological functional properties of injured RGCs.